Fischer–Tropsch Synthesis Bifunctional Catalysts: Cobalt Supported on 3D Mesoporous Cellular Silica Foams Assembled by Using ZSM‐5 Seeds. Issue 20 (5th September 2017) - Wei, Liang; Zhao, Yanxi; Zhang, Yuhua; Liu, Chengchao; Hong, Jingping; Xiao, Qi; Xiong, Haifeng; Li, Jinlin
Abstract: Mesoporous cellular silica foams (MCF) have 3D pore networks in which large spherical cell pores interconnect with small window pores. This novel characteristic provides an open pore structure that favors the accessibility of reactants and mass transfer in reactions. In this work, MCF was functionalized by assembling ZSM‐5 seeds to improve the acidity and the ZSM seed was found to disperse in the MCF structure homogeneously (MCF‐Z). The obtained MCF‐Z materials showed high surface acidity and were then used as supports for cobalt Fischer–Tropsch synthesis (FTS) bifunctional catalysts (20 wt % Co). Compared with Co/MCF catalyst, the Co/MCF‐Z catalysts showed higher CO conversion and improved durability in FTS at 260 °C and 1.0 MPa. Moreover, on increasing the amount of ZSM‐5 seed, the activity of Co/MCF‐Z catalysts gradually increased and then decreased. Co/MCF‐Z catalyst assembled with the highest amount of ZSM‐5 seed (Al/Si=1.5 %, molar ratio) exhibited the lowest deactivation rate, which was owing to the superior stability of the MCF‐Z support and an increased interaction between cobalt and MCF‐Z. The Co/MCF‐Z bifunctional catalyst showed higher iso ‐paraffin/ n ‐paraffin ratios, higher olefin/paraffin ratios as well as lower C2 –C4 alcohol selectivity in comparison to Co/MCF catalyst. For the Co/MCF‐Z catalyst, the decrease in space velocity led to hydrocarbon selectivity shifting toward middle distillate products. Abstract : Well seeded : 3D mesoporous cellular silica foam (MCF) was functionalized by assembling ZSM‐5 seeds to improve the acidity. Compared with Co/MCF, the cobalt bifunctional catalyst supported on the functionalized MCF‐Z shows increased activity, lower deactivation rate, higher iso ‐paraffin/ n ‐paraffin ratio, and lower C2 –C4 alcohol selectivity.